Discursive themes, silences, and contradictions on the democratic role of universities in Iceland. - Bjarnadóttir, Valgerður S.; Ólafsdóttir, Anna; Geirsdóttir, Guðrún (Veftímaritið Stjórnmál og stjórnsýsla, 2019)
The aim of this paper is to explore whether and how discourses in Icelandic public policy documents reflect a) the democratic role of universities and b) universities’ role in preparing students for responsible participation in a democratic society. Key policy documents related to Icelandic universities were analysed. The documents present university policy on three levels; a) the current official policy presented by the national authorities, b) the current policy of individual universities, and c) the most recent annual reports published by each university. These three levels were selected to explore the topic from the stage of formal policy making, to the purposes each university has defined for itself, and to reported actions in the institutions that adhere to the policy. In sum, the findings indicate a lack of conceptualisation of the democratic role of universities in official policies. While the university institutions report on current themes in the international discourse, vaguely related to the critical public and civic role of universities, quality and competitiveness are central discursive themes, obscuring discourses on the democratic role. Markmið þessarar greinar er að varpa ljósi á orðræðu um lýðræðislegt hlutverk íslenskra háskóla með greiningu á ráðandi stefnumótunarskjölum um háskóla. Þær spurningar sem leitast verður við að svara eru hvort og hvernig orðræða í opinberum stefnuskjölum um háskóla endurspeglar a) lýðræðislegt hlutverk háskóla og b) hvernig háskólum er ætlað að búa nemendur undir ábyrga þátttöku í lýðræðissamfélagi. Valin voru til greiningar lykilskjöl þar sem lagaumgjörð og stefna íslenskra háskóla birtist. Skipta má úrtakinu í þrennt, þar sem skjölin draga fram stefnu háskóla á þremur ólíkum stigum; frá heildarstefnu hins opinbera, til þeirra hugmynda og áhersluatriða sem háskólarnir velja að draga fram í stefnum sínum, og til ætlaðrar framkvæmdar eins og hún er sett fram í ársskýrslum skólanna. Niðurstöður greiningarinnar benda til þess að hugmyndir um lýðræðislegt hlutverk ...